KAJIAN LITERATUR KESADARAN SITUASIONAL PILOT DI BIDANG PENERBANGAN - Ahmad Hariri; Parjan (SOSIOEDUKASI, 2022)
Situational awareness is an important aspect that a pilot must have as an operator in the aviation sector. This aspect plays an important role in maintaining safety in flight operations. Situational awareness is also an important material in the education and training of prospective pilots. The situational awareness study among pilots is an important study to do. The purpose of writing this article is to conduct a literature review of pilot situational awareness in the field of aviation. The study was conducted by searching the literature for research publications within the last 25 years. The review is carried out by compiling research summaries sequentially according to the year of publication. Research topic grouping is done to get the amount of research according to the topic and topic area. The analysis is carried out to get an overview of future research trends. The results of the study show that the number of research tends to increase after 2015. While the research topics that are mostly studied are the implementation and analysis of pilot situational awareness.